Pusat Urutan Tradisional Melayu Tawakal / Muhammad Akim Hassan ... [et al.] - Hassan, Muhammad Akim; Zuraidi, Muhammad Amirul Hakim; Isa, Ahmad Syahmi; Jahya, Mohamad Azim (2021)
Massage therapy is a lucrative business that provides healthcare-related services to help individuals recover from illness or to relieve muscle pain, improve sleep, increase their immune function, improve their mental skills, treat headache sufferers, alleviate depression, and reduce stress and anxiety. About our company, we are a massage therapist specialized with a premise in Kuala Lumpur's Kampung Baru. Our company is called Pusat Urutan Tradisional Melayu Tawakal, and we operate as a partnership with four members, two of which are female, for a total of six persons in our company. Also, we provide traditional massage for both genders, including female workers, and we separate massage areas for both genders for the convenience of our customers. Acupuncture and cupping were two of the other procedures we offered. Another information about our company is, we only started in the first quarter of 2019, our company is still in its infancy. For the record, we are qualified massage therapists, and we acknowledge that we are still young and new to this type of business, as this type of business is typically handled by people aged 30 and up.